Islamic Social Reporting: Influencing Factors and Impact on Firm Value (Study of Islamic Banks) - Anita Dwi Utami; Tettet Fitrijanti; Citra Sukmadilaga (Budapest International Research and Critics University, 2022)
Islamic banking is the largest sector in the Islamic finance industry. Good bank performance can certainly add to a positive image so that it can result in company value. The covid-19 pandemic has made a person's survival dependent on others who provide assistance and donations, where this is included in the disclosure of corporate social responsibility as a form of accountability for Islamic banks to fellow humans and Allah SWT. The purpose of this study is to determine the board of directors, sharia supervisory board, and customer pressure can affect the disclosure of Islamic social reporting and have an impact on firm value. The research method used in this research is explanatory research with a quantitative approach. Analysis of research data using panel data regression analysis. The research sample is 62 Islamic banks from 9 countries with the time of 2019 and 2020. The results show that the sharia supervisory board has a significant negative effect on Islamic social reporting, customer influence has a significant positive effect on Islamic social reporting, and customer influence has a significant positive effect on firm value.